Identification of Indian mustard (Brassica juncea L.) varieties by DUS testing using morphological characters (Journal of Oilseed Brassica, 2026)
Indian mustard [Brassica juncea (L.) Czern & Coss.] varieties were identified through distinctiveness, uniformity and stability (DUS) testing protocol on the basis of experiment conducted during 2013-14 and 2014-15 consecutive years. The experimental procedure was carried as per official guideline of Indian mustard (PPV & FRA, 2009). The selected mustard varieties were identified based on six morphological characters that had capability to separate varieties into groups. Further they were classified based on three qualitative characters viz., leaf hairiness, time of 50% flowering and maturity period, three quantitative characters viz., number of siliqua on main shoot, seeds per siliqua, and weight of 1000 seeds. The varieties PCR-7, Pusa Jaikisan, RH-781 and CS-52 were identified separately on the basis of hairiness, number of siliqua on main shoot and number of seeds per siliqua respectively. All the remaining varieties were classified into groups based on time of 50% flowering, maturity period and weight of 1000 seeds. Thus the present study concludes that morphological characters of DUS protocol prove to be very useful and convenient for varietal identification which in turn helps in maintenance of genetic purity of varieties.